How Facebook Still Matters: the Battle of Campaign Strategy in Bantul Election - Rahmad Agus Dwianto; Arief Bakhtiar Darmawan; Joko Santoso; Achmad Nurmandi; Eko Priyo Purnomo; Suswanta Suswanta (FISIP UPNVJ, 2025)
This study aims to analyze digital political campaigns using Facebook Ads. Political campaigns in this digital era are carried out through social media to attract the engagement of prospective voters. This research uses a case study of the Facebook ads campaign of one of the winning pairs for the regional head election in Bantul, Indonesia. Facebook as a social media for campaigning. The results of this study indicate that the Facebook Ads campaign successfully reached the target audience. The total reach during the 30 days ad serving period was 646,142. This figure is categorized as high because when compared to the number of voters registered in the final voter list for the Bantul election (704,688), this figure has reached most of the targeted voters. Similar to reach, Facebook Ads campaign impression data also fluctuated during the ad serving period. The total number of impressions during 30 days of ad serving was 669,149. The more often the ad appears on the users’ Facebook page, the greater the opportunity for the ad to be read and observed by the audience.